2012
DOI: 10.1007/s10895-011-1035-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Benzanthrone Aminoderivatives for Membrane Studies

Abstract: The potential of novel benzanthrone aminoderivatives to trace the changes in physicochemical properties of lipid bilayer has been evaluated. Binding of the dyes to the lipid bilayers composed of zwitterionic phospholipid phosphatidylcholine (PC) and its mixtures with anionic phospholipid cardiolipin (CL) and cholesterol (Chol) was followed by significant quantum yield increase with small blue shift of emission maximum. Analysis of partition coefficients of the dyes under study showed that all aminobenzanthrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Later, several benzanthrone dyes were synthesized to verify changes in the physicochemical properties of a lipid bilayer (Trusova et al, 2012;Ryzhova et al, 2016), and to identify and characterize fibrillar aggregates of lysozyme (Vus et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, several benzanthrone dyes were synthesized to verify changes in the physicochemical properties of a lipid bilayer (Trusova et al, 2012;Ryzhova et al, 2016), and to identify and characterize fibrillar aggregates of lysozyme (Vus et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bright fluorescence, high extinction coefficient, photo-, thermo-and chemical stability, and reduced background signal make benzanthrone dyes particularly attractive as bio-imaging agents (Yang et al, 1999). Our previous study demonstrated high lipidassociating ability of a series of newly synthesized benzanthrone amino and amidino derivatives (Trusova et al, 2012;.…”
Section: Introductionmentioning
confidence: 98%
“…Despite wide technological utilization of these compounds, their applicability as fluorescent probes in biological assays (amyloid fibril identification, cell membrane and DNA structure investigation) is continuously growing . Therefore, it is very important to synthesize new benzanthrone class compounds and to investigate their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The benzanthrone dyes, a well-known class of fluorescent probes that emit in the spectral region from yellow-green to red-purple (depending on the dye structure), have found diverse applications in biomedical research and diagnostics due to their favorable spectral characteristics, such as a large extinction coefficient, a marked Stokes shift; negligible fluorescence in an aqueous phase, etc [1][2][3][4][5][6][7][8][9][10]. Specifically, it has been shown that the benzanthrone dye in combination with the thin polylactic acid film is capable of displaying the antimicrobial activity against Gram-positive and Gramnegative bacteria [11].…”
mentioning
confidence: 99%